Primary angiosarcoma of the breast: a case report - Im, Soyoung (Int J Clin Exp Pathol, 2019)
Background: Primary angiosarcoma of the breast is extremely rare, accounting for less than 0.05% of all primary malignancies of the breast. Here, we report here a case of primary angiosarcoma with full description of radiology and histology, including electron microscopic findings. Case presentation: A 39-year-old woman complained of a diffuse hard mass in her right breast. She did not have any history of radiation exposure. Ultrasonography revealed a 7 cm sized mass with an irregular anechoic cystic portion replacing the entire right breast. Modified radical mastectomy was performed. The diagnosis of intermediate grade angiosarcoma was made by microscopic examination, immunohistochemical staining, and electron microscopic examination. The patient underwent four cycles of adriamycin-ifosfamide chemotherapy and received radiation therapy. Multiple bone metastases occurred 9 months after surgery and palliative treatment was given. Follow up was lost at post-operative 22 months. Conclusions: We report a rare case of intermediate grade primary angiosarcoma with detailed radiological and histological findings. Despite postoperative chemoradiation therapy, multiple metastases suggest that intermediate grade may have a more aggressive behavior.